2006
DOI: 10.1016/j.compositesa.2005.05.036
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fiber surface treatments on the tensile and water sorption properties of polypropylene–luffa fiber composites

Abstract: The effects of coupling agents on the mechanical, morphological, and water sorption properties of luffa fiber (LF)/polypropylene(PP) composites were studied. In order to enhance the interfacial interactions between the PP matrix and the luffa fiber, three different types of coupling agents, (3-aminopropyl)-triethoxysilane (AS), 3-(trimethoxysilyl)-1-propanethiol (MS), and maleic anhydride grafted polypropylene (MAPP) were used. The PP composites containing 2-15 wt% of LF were prepared in a torque rheometer. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
195
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(213 citation statements)
references
References 21 publications
14
195
0
4
Order By: Relevance
“…The water absorption increased with increasing KNF loading for both composites. The water absorption of cellulose fiber composites resulted from the formation of hydrogen bonds between hydroxyl groups of cellulose and water molecules (Demir et al 2006). Majid et al (2010) found that the water absorption of LDPE/TPSS-kenaf fiber composites was a consequence of the hydrophilic nature of both kenaf fiber and starch.…”
Section: Fourier Transform Infrared Spectroscopymentioning
confidence: 99%
“…The water absorption increased with increasing KNF loading for both composites. The water absorption of cellulose fiber composites resulted from the formation of hydrogen bonds between hydroxyl groups of cellulose and water molecules (Demir et al 2006). Majid et al (2010) found that the water absorption of LDPE/TPSS-kenaf fiber composites was a consequence of the hydrophilic nature of both kenaf fiber and starch.…”
Section: Fourier Transform Infrared Spectroscopymentioning
confidence: 99%
“…Using natural fibres in polymer composites reduces the market cost, promotes global sustainability, and increases commercial use in various applications (Jawaid et al 2011). However, there are limitations to using natural fibres as a reinforcing material because of their poor wettability, high moisture absorption tendency, poor adhesion with synthetic materials, and low thermal stability during processing (Demir et al 2006). Oil palm empty fruit bunch (EFB) fibres are considered as agricultural wastes and renewable resources.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, adhesion is improved and the voids within the surface of these materials become smaller. This happens while the water absorption is decreased (Demir et al 2006).…”
Section: Effect Of Acetylation On Water Absorption and Thickness Swelmentioning
confidence: 99%
“…The trend of water absorption and thickness swelling in the wood plastic has been studied by numerous researchers (Tajvidi et al 2006;Shi and Gardner 2006). Moreover, much research has been done on chemical treatment of wood fibers in order to reduce the water absorption and thickness swelling; also, this research has shown improved dimensional stability of wood plastic (Tserki et al 2005;Demir et al 2006;Dominkovics et al 2007). Polarity of the hydroxyl groups on the surface of the lignocellulose materials is an obstacle against the formation of a chemical bond with the polymer.…”
Section: Introductionmentioning
confidence: 99%